Anaerobic digestion of cornmeal – the effect of crude enzyme extract and co‐digestion with cow manure. (23rd October 2021) - Pinheiro, Vanessa Elisa; Wainaina, Steven; Polizeli, Maria de Lourdes Teixeira de Moraes; Horváth, Ilona Sárvári
Abstract: This study examined the effect of a crude enzyme extract, containing mainly starch‐degrading enzymes, on cornmeal ( Zea mays ) hydrolysis. This was followed by an investigation of the effect of enzymatic treatment for the anaerobic digestion of this biomass. Cornmeal and cow manure were also co‐digested, and both batch and semi‐continuous experiments were performed. The enzymatic pretreatment of cornmeal resulted in a yield of 65 ± 5% reducing sugars, with 1:10 w/v (grams of dry substrate per mililiters of enzyme extract) enzyme load at 45 °C for 48 h. There was an 8% enhancement of methane production observed during the batch assays, both when cornmeal hydrolysate was digested and when enzymes were added directly to the digester. Synergetic effects were found when co‐digesting cornmeal and cow manure, leading to higher methane yield (280 NmL gVS –1 ) than that (200 NmL gVS –1 ) calculated based on the methane potential of the individual substrates. Regarding long‐term effects, the laboratory‐scale semi‐continuous experiments also demonstrated that the co‐digestion of cornmeal and cow manure (1:1 volatile solid ( VS ) basis) led to a stable process reaching an organic loading rate of 3 g VS  L day –1 and achieving a daily methane production of 1280.12 ± 99.4 NmL CH4 /day. However, when cornmeal was investigated in mono‐digestion, and the enzyme extract was directly added during semi‐continuous digestion of cornmeal, volatile fatty acid (VFA) accumulation was observed, leading to a decrease in pH, and no significant enhancement of the conversion into methane was observed. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd